Physical Activity and Adolescent Health: What Should We Know? - , Luiz Antonio Del Ciampo; , Regina Lopes Del Ciampo (Archives of Current Research International, 2020)
Adolescence is characterized by a period of physical, emotional, social and cultural transformations, significant increase in size and changes in physical appearance. At this stage of life the individual is very susceptible to influences of the environment, nutrition, climate, interpersonal relationships and physical activity, among others. This article presents some of the main physical and emotional characteristics of adolescence and the importance of physical activity, highlighting the benefits for physical and mental health, and proposing actions to increase this practice among adolescents.